Energy Policies and the Mexican Economy - World Bank (Washington, DC, 2014)
The report looks at energy policies in Mexico (both a major energy producer, and consumer) within its economic context, how the energy sector is managed, and how it performs, and at the implications for economic growth and public finances, and by extension, for broader social policies which depend heavily on federal funding. The energy sector finds itself in a vicious circle - reduced budget and borrowing capacity are leading to insufficient sector investment - resulting in declines in future production, hence government revenue. Breaking this vicious circle is a major challenge, given that attracting finance for energy sector investment on a major scale, without government support, lies at the heart of the problem. The report reviews the choices to increase efficiency, and electricity subsidies, as well as those for efficiently expanding oil and gas output. Three key areas for reform are discussed: a) achieving permanent gains in operational efficiency of the power and hydrocarbons sectors, to lower costs and improve service quality; b) restructuring electricity subsidies, targeting the poorest households; and, c) opening the hydrocarbons sectors to new players, attracting funds and skills, needed to undertake exploration, and development of the country's oil and gas resources. A policy simulation outlines the potential dynamic, general equilibrium model, assessing the economic impact of alternative energy policies. The analysis indicates that whereby an overoptimistic picture of the economic performance results from weak employment and wage estimates, conversely, the importance of increasing oil production will be undervalued, if the wage constraint is ignored, since this may be the single most important variable for ensuring that the real wage constraint does not bite.